Advances in the sociology of trust and cooperation. Theory, experiments, and field studies - Corten, Rense (De Gruyter, 2020)
The problem of cooperation and social order is one of the core issues in the social sciences. The key question is how humans, groups, institutions, and countries can avoid or overcome the collective good dilemmas that could lead to a Hobbesian war of all against all. Using the general set of social dilemmas as a paradigmatic example, rigorous formal analysis can stimulate scientific progress in several ways. The book, consisting of original articles, provides state of the art examples of research along these lines: theoretical, experimental, and field studies on trust and cooperation. The theoretical work covers articles on trust and control, reputation formation, and paradigmatic articles on the benefits and caveats of abstracting reality into models. The experimental articles treat lab based tests of models of trust and reputation, and the effects of the social and institutional embeddedness on behavior in cooperative interactions and possibly emerging inequalities. The field studies test these models in applied settings such as cooperation between organizations, informal care, and different kinds of collaboration networks. The book will be exemplary for rigorous sociology and social sciences more in general in a variety of ways: There is a focus on effects of social conditions, in particular different forms of social and institutional embeddedness, on social outcomes. Theorizing about and testing of effects of social contexts on individual and group outcomes is one of the main aims of sociological research. Modelling efforts include formal explications of micro-macro links that are typically easily overlooked when argumentation is intuitive and impressionistic Extensive attention is paid to unintended effects of intentional behavior, another feature that is a direct consequence of formal theoretical modelling and in-depth data-analyses of the social processes